Determinants of Workforce Preparedness during Pandemics Among Healthcare Workers at the U.S. Department of Veterans Affairs - Michelle D. Balut; Claudia Der-Martirosian; Aram Dobalian (SAGE Publishing, 2021)
Objective: An infectious disease outbreak can place a significant burden on healthcare systems, however, our understanding of the broader healthcare workforce's preparedness during a pandemic is limited. This study examines factors that influence perceived workforce preparedness at the U.S. Department of Veterans Affairs (VA) during a pandemic. Methods: The VA Preparedness Survey was a random, anonymous, web-based survey fielded nationwide October to December 2018. Multivariate statistical analyses examined the effects of study relevant factors (sociodemographic, work-related, general health, and household-related characteristics of VA employees) on perceptions of workforce preparedness, including institutional readiness and understanding of individual roles during a pandemic. Results: Four thousand and twenty-six VA employees responded. Overall, 55% were confident in their VA medical facility's ability to respond; 49% understood their role; and 68% reported their role to be important during a pandemic. After controlling for study-relevant factors, household preparedness, having plans that address the health care needs of family members, and higher self-reported health status were associated with all 3 workforce preparedness variables. Clinical staff (compared to non-clinical staff) were less likely (OR:0.80, 95% CI:0.68-0.94, P  < .01) to have confidence in their medical facility's ability to respond but more likely (OR:1.77, 95% CI:1.49-2.10, P  < .001) to believe their role was important. Employees who have been at the VA longer (OR:1.07, 95% CI:1.01-1.14, P  < .05) or have experienced a disaster while working at the VA (OR:1.29, 95% CI:1.04-1.59, P  < .05) were more likely to understand their role during a pandemic. Conclusion: The findings from this study suggest the need for identifying ways to increase VA employees' confidence in their medical facility's ability to respond to a pandemic; develop trainings to improve understanding of their different yet critical roles, for both clinical and non-clinical staff, during a pandemic; create different workforce trainings for newly hired employees; and identify ways to improve household preparedness for a pandemic outbreak.